2007
DOI: 10.1590/s1677-04202007000200002
|View full text |Cite
|
Sign up to set email alerts
|

An instrumental set up for seed germination studies with temperature control and automatic image recording

Abstract: This paper describes a new instrumental methodology proposed for the study of seed germination which can be applied to germination physiology, agriculture and forest restoration. This instrument performs the recording of images of germinating seeds through the use of a flat-bed scanner coupled to a computer, where a specific program commands the capture of these images at predetermined time intervals. These images are archived for posterior analysis. The device allows the collection of data and the elaboration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
3
1
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…In this type of large experiments it is difficult to manually score germination at multiple time points per day for a number of days or weeks. Although major progress for semi‐automated scoring of seed germination of Lactuca sativa , using a flat‐bed scanner, was made by Teixeira et al. (2007), the setup suggested by these authors only allows a limited number of samples.…”
Section: Introductionmentioning
confidence: 99%
“…In this type of large experiments it is difficult to manually score germination at multiple time points per day for a number of days or weeks. Although major progress for semi‐automated scoring of seed germination of Lactuca sativa , using a flat‐bed scanner, was made by Teixeira et al. (2007), the setup suggested by these authors only allows a limited number of samples.…”
Section: Introductionmentioning
confidence: 99%
“…These systems can generate high quality images at a high temporal resolution, and can be scaled by increasing the number of scanners. However, precise light control during growth is challenging and the cost of scaling may be prohibitive (Slovak et al 2014; Teixeira et al 2007). Teixeira et al 2007 demonstrated humidity and temperature regulation, but not light control.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, many CV and ML combined analytic methods have been developed to enable the automation of organ‐level phenotypic analysis, including leaves, roots, and reproductive organs (Pound et al ., 2017; Sadeghi‐Tehran et al ., 2017; Xiong et al ., 2017; Zhou et al ., 2017a; Yasrab et al ., 2019). By combining colour, texture, morphologies, and growth patterns, seed germination can be quantified in a dynamic and objective manner, based on which large‐scale and reproducible evidence can be produced to enable new biological discoveries for seed physiology (Teixeira et al ., 2007; Demilly et al ., 2015; Reyazul et al ., 2015; Lurstwut & Pornpanomchai, 2017; Elmasry et al ., 2019). Furthermore, the automation of seed germination scoring presents a good opportunity to initiate the standardisation of seed science research.…”
Section: Introductionmentioning
confidence: 99%